Heritage trees of Penang - Gardner, Simon (Areca Books, 2011)
A celebration of 200 trees which form an integral part of the natural, cultural and urban heritage of Penang. This unique book covers a wide range of both forest and cultivated species, each with a special story to tell. Taken as a whole Heritage Trees of Penang weaves a rich tapestry of the past and present that demonstrates why Penang is such a remarkable place. Richly illustrated with 72 original watercolours and over 1200 photographs, this invaluable guide is a beautiful and authoritative companion to Penang's botanical inheritance.